The advertising of barbershop influences consumer / Zarif Adly Zainudin - Zainudin, Zarif Adly (2015)
Advertising is fast of powerful medium to advertise in the new millennium. With the number of advertisements increasing, the new medium is viewed as the advertiser's dream. Advertising is becoming a part of companies marketing strategy however it requires new strategies and thinking. The benefits of advertising are its ability its cover people from different geographical area with varied tastes and preferences. This study is descriptive study and the sampling technique here is used convenience sampling. The sample size is for 50 selected people from the population of Johor Bahru City. The data is collected with the help of structured questionnaires, which is includes open end and close-ended questions. The next step in the research process is Analysis and Interpretation of the Data Collected from the respondents. This analysis and interpretation is done with the help of graphs and tabulation. They are prepared with the help of MS Word and Excel software With the help of analysis and interpretation the findings are drawn which includes whether consumers are aware of advertising, do advertisements effect their purchase behavior. With the critical analysis and interpretation the suggestions and recommendations are drawn on how to improve advertisement in order to attract much of the viewership and to increase the purchasing efficiency and also improve the methods of advertisements Finally, the conclusion where the briefing and the topics aspects is been given with few suggestions and recommendations, finally concludes the project report